Native Beef Collagenase MMP-9 May Contribute to Tenderness Improvement by Degrading Connective Tissues in Extended Aged Beef - L. A. Koulicoff; A. A. Welter; P. A. Hammond; C. K. Chun; T. G. O'Quinn; G. Magnin-Bissel; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:Collagen is one of the main components in the connective tissue (CT) and contributes to background toughness in beef. It is known that in living animals, collagen can be degraded and remodeled by collagenase matrix metalloproteinases (MMP); however, it is unclear if collagenase MMP can impact CT texture during postmortem aging of beef. Therefore, this study aimed to understand how collagenase MMP activity may impact postmortem connective tissue degradation in beef in three different cuts and four different aging periods. Study Description:Beef boneless striploin, top sirloin butt, and heel were acquired from 10 U.S. Department of Agriculture high choice beef carcasses and assigned to be aged for 3, 21, 42, or 63 days (n = 120). Following each aging time, Warner-Bratzler shear force (WBSF), connective tissue shear force (CTSF), trained panel responses, collagen content, denaturation temperature of connective tissue, collagen crosslinks density, connective tissue degradation product, and native collagenase activity were measured, and collagenase identity was identified as MMP-9 through Western blot. Results:Striploin was considered the most tender muscle (P<0.01), and tenderness was improved (P<0.01) after 21 days of aging. In addition, CTSF data and trained panelists demonstrated softening (P<0.05) of CT after 21 days of aging. Heel and top sirloin butt did not differ (P>0.10) in collagen content and had greater (P<0.01) collagen content than striploin. However, no aging effect was found for collagen content (P>0.10). Denaturation temperature of CT decreased and collagen crosslinks density increased after 42 days of aging for all cuts evaluated in this study (P<0.01). The MMP-9 activity decreased (P<0.01) from 3 to 21 to 42 days, and it had the greatest (P<0.01) activity in heel compared to the other two cuts. Heel and striploin had greater (P<0.01) connective tissue degradation product than top sirloin butt. It was interesting to note that while striploin and heel showed a decrease (P<0.05) in the degradation product from 3 to 21 to 42 days, top sirloin butt did not show any changes (P>0.10) in degradation product during the entire 63 days of aging period. The Bottom Line:These results provide an explanation on CT softening during postmortem aging. Understanding the mechanism of tenderness improvement from the softening of CT may help the industry improve the eating quality of lower quality beef cuts.
Keywords: connective tissue; matrix metalloproteinases; tenderness